A Phosphine‐Coordinated Boron‐Centered Gomberg‐Type Radical1. (26th June 2015) - Rosenthal, Amos J.; Devillard, Marc; Miqueu, Karinne; Bouhadir, Ghenwa; Bourissou, Didier
Abstract The P‐coordinated boryl radical [Ph2P(naphthyl)BMes]. (Mes=mesityl) was prepared by (electro)chemical reduction of the corresponding borenium salt or bromoborane. Electron paramagnetic resonance (EPR) analysis in solution and DFT calculations indicate large spin density on boron (60–70 %) and strong P–B interactions (P→B σ donation and B→P negative hyperconjugation). The radical is persistent in solution and participates in a Gomberg‐type dimerization process. The associated quinoid‐type dimer has been characterized by single‐crystal X‐ray diffraction.